2010
DOI: 10.1111/j.1442-2042.2010.02592.x
|View full text |Cite
|
Sign up to set email alerts
|

Late toxicity after conformal and intensity‐modulated radiation therapy for prostate cancer: Impact of previous surgery for benign prostatic hyperplasia

Abstract: Objectives:To retrospectively compare late toxicity of conventional-dose three-dimensional conformal radiation therapy (3D-CRT) and high-dose intensity-modulated radiation therapy (IMRT) for prostate cancer. Methods: A total of 340 patients with T1-3 prostate cancer were treated with 3D-CRT (n = 228) and IMRT (n = 112). The median follow-up time was 5.9 years and 3.0 years, respectively. The prescription dose was 70 Gy for 3D-CRT and 78 Gy for IMRT. Late gastrointestinal (GI) and genitourinary (GU) toxicities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Dose escalation without enhancing toxicity is thus possible if IMRT is used instead of 3D-CRT. The results of several other studies support this conclusion: a 16% incidence of urinary toxicity and 3% incidence of GI toxicity (grade 2+) 10 years after 81 Gy IMRT, a 9% incidence of grade 2 urinary toxicity and a 5% incidence of grade 2 GI toxicity 3 years after 76 Gy IMRT, and no difference in urinary or GI toxicity between 78 Gy IMRT and 70 Gy 3D-CRT [31-33]. …”
Section: Discussionmentioning
confidence: 77%
“…Dose escalation without enhancing toxicity is thus possible if IMRT is used instead of 3D-CRT. The results of several other studies support this conclusion: a 16% incidence of urinary toxicity and 3% incidence of GI toxicity (grade 2+) 10 years after 81 Gy IMRT, a 9% incidence of grade 2 urinary toxicity and a 5% incidence of grade 2 GI toxicity 3 years after 76 Gy IMRT, and no difference in urinary or GI toxicity between 78 Gy IMRT and 70 Gy 3D-CRT [31-33]. …”
Section: Discussionmentioning
confidence: 77%
“…A recent systematic review of IMRT identified five published studies in which late toxicity data was compared between IMRT and CRT, and we identified one additional study based on a comprehensive search (7, 4146). Table 5 summarizes these studies and compares results to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Použití radioterapie s modulovanou intenzitou umožňuje eskalovat dávku při Významným faktorem ovlivňujícím míru chronické toxicity je rovněž čas [26][27][28][29]. Naprostá většina symptomů pozdní postradiační gastrointestinální toxicity je pozorována v prvních třech letech po ukončení radioterapie.…”
Section: Závěrunclassified